Digital (Electronic) Paid Provision of Services in the Field of Legal Activity - Karasheva, Zhanar; Assanova, Saida; Nurakhmetova, Gulmira; Nuranova, Raikhan (Law, State and Telecommunications Review, 2024)
[Background] The growing role of information technology in the activities of legal practitioners, lawyers, notaries, and judicial authorities highlights the importance of addressing the problem. Additionally, the lack of comprehensive studies in modern legal literature regarding the essence of digital paid assistance in the field of legal activity underscores the need for research in this area. [Purpose] The study’s purpose is to address the growing significance of information technology in various legal professions, including legal practitioners, lawyers, notaries, representatives of judicial authority, and law enforcement agencies. [Methodology/Approach/Design] The following research methods are the main ones in this scientific work: systemic-legal, formal-legal, comparatively legal, as well as historical, logical, and dialectical methods. Due to these methods, it became possible to determine the essence of digital paid services in the field of legal activity, to reveal their features, as well as identify their problems and develop ways to improve such services. [Findings] During the course of this study, several significant results were obtained. Firstly, the concept of digital paid legal services was elucidated, and the main types of such services were identified, along with their distinctive characteristics. Furthermore, the study highlighted both the positive and negative aspects of providing these services, emphasizing their significance in the development of legal science and the legal profession as a whole. [Originality/Value] The study is significant as it addresses the need for an effective legal framework to regulate digital services in the field of legal activity in Kazakhstan. It highlights the lack of comprehensive legislation and the slow integration of digital technologies into the legal sector. By exploring the challenges and providing recommendations, the study aims to facilitate the adoption of innovative technologies and improve the quality of legal services in the country.